IEEE 1149.1 compliance-enable pin(s): a solution for embedded microprocessor-based systems debug and test - Alves, Gustavo R. (2017)
Microprocessor-based systems are usually debugged with the help of in-circuit emulators and logic analysers. However, these traditional debug tools cannot be used when the microprocessor is an embedded core. To overcome this problem we propose the use of an embedded debug and test infrastructure and the IEEE 1149.1 compliance-enable mode to implement the basic functionality provided by an In-circuit emulator and a logic analyser.